(untitled) (Global Journal of Medical Research, 2020)
Equine infectious anemia (IEA) is a worldwide distribution disease caused by a lentivirus associated withthe presence of transmitting vectors of the gender Tabanus and equines by producing anemiaandconsequently hypoxia that produces a multi-organ deterioration. The presence of AIE in the working equine of San Andr#xE9;s Itzapa, Chimaltenango was evaluated. This in order to assess the presence of the disease since this group of equines is part of the food security of the community. 100 blood samples were analyzed using the gel agar immunodi-fusion test. The presence of the disease was found in 8% of the sampled animals.